Hepatocellular Carcinoma Complicated by Echinococcal Cyst: A Case Report - Guo, Jiwu; Ma, Chenzhe; Song, Xuewen; Tang, Futian; Guo, Lingyun; Mao, Jie; Li, Yumin (Frontiers in Surgery, 2022)
Hepatocellular carcinoma (HCC) combined with hepatic hydatid disease is a rare clinical case, having certain specificity in clinical diagnosis and treatment. We report a case of HCC combined with hepatic hydatid disease treated in our clinic, to arouse the attention of clinicians to the disease. A 54-year-old female patient was admitted to the clinic on Oct. 31, 2016 due to "Intermittent upper abdominal pain and discomfort for 1 month". Abdominal computed tomography (CT) in the previous hospital showed liver space-occupying lesions, and hepatic hydatid disease should be considered. The patient had a history of Hepatitis B virus (HBV) infection since childhood but has not received antiviral treatment. She did have a history of life in pastoral areas. Laboratory examination: Alpha-fetoprotein (AFP) 1210 ng/ml, HBV DNA: 5.32E+03 IU/ml. Casoni test was positive. Enhanced CT of abdomen suggestion: liver malignant tumor, hepatic hydatid disease. While the gastroscopy and colonoscopy showed no abnormalities. She received the operation on Nov. 10, 2016. Hepatic Segment 5, 8 segments, Echinococcus Internal Capsule, and Cholecyst were removed. She has taken albendazole (0.4g/day) for 6 months and oral entecavir (0.5mg/day) antiviral treatment for a long time after surgery. From May 2017 to Oct. 2019, a total of 5 cycles of transarterial chemotherapy embolization (TACE) were performed. The patient underwent surgical treatment, followed by TACE, antiviral therapy, and sequential albendazole treatment. The AFP level increased significantly, but there was no obvious recurrence of HCC in imaging.